Afferent Loop Syndrome Due to Volvulus of the Afferent Limb. Issue 7 (July 2019) - Desai, Aditi; Manvar, Amar; Ho, Sammy
Abstract : ABSTRACT: A 78-year-old woman with a history of stage IIB gastric adenocarcinoma with previous Billroth II subtotal gastrectomy was admitted with pancreatitis, with subsequent development of fevers and acute jaundice. Transabdominal ultrasound demonstrated bile duct obstruction. An endoscopic retrograde cholangiopancreatography was attempted, but the lumen of the afferent limb appeared distorted without an obstructing lesion. A computed tomography scan demonstrated volvulus of the afferent limb near the gastrojejunal anastomosis, with afferent limb dilation and significant biliary dilation.